Analysis of Debt to Equity Ratio (DER), Return On Assets (ROA), Fixed Asset Turnover (FATO), and Earning Per Share (EPS) on Stock Prices in Transportation Sector Companies on the IDX in 2020-2021 - Kinasih, Roro Budi; Yoganingsih, Tutiek (Kirana Publisher (KNPub), 2023)
This study aims to analyze: (1) the effect of return on assets (ROA) on stock prices in transportation sector companies, (2) the effect of debt to equity ratio (DER) on stock prices in transportation sector companies, (3) the effect of fixed assets turnover ratio (FATO) on stock prices in transportation sector companies, (4) the effect of earning per share (EPS) on stock prices in transportation sector companies. The populations in this study were 30 companies from the transportation subsector that have been listed on the Indonesia Stock Exchange (IDX). The sampling technique used purposive sampling technique. Data collection was carried out using documentary methods. The data analysis technique used is the classical assumption test and hypothesis testing with panel data regression analysis. The results of the study after the data were processed through the help of the EViews 9 program. Data testing is continued with the classical assumption test where from the results of the classical assumption test it can be stated that the data does not have multicolonierity and the data does not occur heteroscedasticity problems. The results of this study indicate that ROA has a positive and significant effect on the share price of companies listed in the Transportation sector on the IDX in 2020-2021. However, DER, TATO, and EPS are not significant while on the stock prices of companies listed in the Transportation sector on the IDX in 2020-2021.